Complexation of Cm(iii) with the recombinant N-lobe of human serum transferrin studied by time-resolved laser fluorescence spectroscopy (TRLFS). Issue 4 (8th December 2014) - Bauer, N.; Smith, V. C.; MacGillivray, R. T. A.; Panak, P. J.
Abstract : The complexation of Cm(iii ) with the recombinant N-lobe of human serum transferrin hTf/2N is investigated using TRLFS. The results reveal significant differences in the complexation properties of transferrin and the half molecule. Abstract : The complexation of Cm(iii ) with the recombinant N-lobe of human serum transferrin (hTf/2N) is investigated in the pH range from 4.0 to 11.0 using TRLFS. At pH ≥ 7.4 a Cm(iii ) hTf/2N species is formed with Cm(iii ) bound at the Fe(iii ) binding site. The results are compared with Cm(iii ) transferrin interaction at the C-lobe and indicate the similarity of the coordination environment of the C- and N-terminal binding sites with four amino acid residues of the protein, two H2 O molecules and three additional ligands ( e.g. synergistic anions such as carbonate) in the first coordination sphere. Measurements at c (carbonate)tot = 0.23 mM (ambient carbonate concentration) and c (carbonate)tot = 25 mM (physiological carbonate concentration) show that an increase of the total carbonate concentration suppresses the formation of the Cm(iii ) hTf/2N species significantly. Additionally, the three Cm(iii ) carbonate species Cm(CO3 ) +, Cm(CO3 )2 − and Cm(CO3 )3 3− are formed successively with increasing pH. In general, carbonate complexation is a competing reaction for both Cm(iii ) complexation with transferrin and hTf/2N but the effect is significantly higher for the half molecule. At c (carbonate)tot = 0.23 mM the complexation of Cm(iii ) with transferrin and hTf/2N starts at pH ≥ 7.4. At physiological carbonate concentration the Cm(iii ) transferrin species II forms at pH ≥ 7.0 whereas the Cm(iii ) hTf/2N species is not formed until pH > 10.0. Hence, our results reveal significant differences in the complexation behavior of the C-terminal site of transferrin and the recombinant N-lobe (hTf/2N) towards trivalent actinides.